The AfD's Winning Formula – No Need for Economic Strategy Blurring in Germany - Matthias Diermeier (Intereconomics, 2020)
Western European Populist Radical Right Parties (PRRPs) have addressed the dispersed socio-economic status of their electorates by blurring their economic positioning. This contribution analyses the rise of the German PRRP Alternative für Deutschland (AfD) between 2013 and 2017 and the role of its economic policy platform. In contrast to its European peers, the AfD shows few signs of economic strategy blurring. The party offers clear antiredistribution policies that are matched by AfD voters' preferences: even the least affluent AfD supporters have stronger preferences for lower redistribution than the most affluent non-AfD supporters. For AfD supporters with lower socio-economic positions this means that they support economic policies that are against their economic interests. Extreme authoritarian cultural policies spiced up with criticism of the establishment and combined with a general opposition to redistribution can be identified as the AfD's winning formula. Within the Western European PRRP party family, this winning formula directed at supporters with lower socioeconomic positions constitutes an exception.
Keywords: 330